3D characterization of partially recrystallized Al using high resolution diffraction contrast tomography. (December 2018) - Sun, Jun; Yu, Tianbo; Xu, Chaoling; Ludwig, Wolfgang; Zhang, Yubin
Abstract: Synchrotron diffraction contrast tomography (DCT) is for the first time used to characterize recrystallized grains in partially recrystallized Al. The positions, orientations and 3D shapes of >900 recrystallized grains are reconstructed within a gauge volume. The results are compared with those obtained using electron backscattered diffraction based on a statistical analysis. It is found that recrystallized grains with size larger than 10 μm, corresponding to ~98% of the total recrystallized volume of the sample, are well characterized by DCT. The advantages of DCT for recrystallization studies and new possibilities with DCT on new generation synchrotron sources are discussed. Graphical abstract: Unlabelled Image